ChemInform Abstract: Epoxy and Aziridinyl Enolsilanes in Diastereoselective Inter‐ and Intramolecular Friedel—Crafts Alkylations. Issue 32 (22nd July 2016) - Ling, Jesse; Lam, Sze Kui; Lo, Brian; Lam, Sarah; Wong, Wing‐Tak; Sun, Jian; Chen, Guanhua; Chiu, Pauline
Abstract: Intermolecular alkylations with optically‐enriched epoxides are found to occur with preservation of e.e.